Pengaruh Inflasi, Nilai Tukar Rupiah (USD), Suku Bunga Dan Ekspor Terhadap Cadangan Devisa Negara Indonesia Tahun 2009-2019 - Indro Suwarno; I Made Wianto Putra; I Nyoman Sutapa (Jurnal Riset Akuntansi Warmadewa, 2021)
The purpose of the research was to find out and test the influence of independent variables (Inflation, Rupiah Exchange Rate, Interest Rate and Export) on dependent variables (Foreign Exchange Reserves of Indonesia). This research was conducted in Indonesia using time series data obtained from the Central Statistics Agency and Bank Indonesia from 2009-2019. This research data analysis method uses multiple linear regression analysis namely Classical Assumption Test and data processed using IBM SPSS computer program, for testing this research hypothesis researchers use t Test, F Test and Determination Coefficient. From the results of simultaneous testing, it can be concluded that inflation, rupiah exchange rate, interest rate, and export affect Indonesia's foreign exchange reserves. While the test results can be partially concluded that Inflation has no effect on Indonesia's foreign exchange reserves, rupiah exchange rate has a positive and significant effect on Indonesia's foreign exchange reserves, interest rates have no effect on foreign exchange reserves in Indonesia, exports have a positive and significant effect on foreign exchange reserves in Indonesia.